2015
DOI: 10.1111/echo.12965
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dyssynchrony by Three‐Dimensional Echocardiography: Current Understanding and Potential Future Clinical Applications

Abstract: Left ventricular mechanical dyssynchrony is an important prognostic factor for patients with symptomatic systolic heart failure and has emerged as a therapeutic target for cardiac resynchronization therapy (CRT). However, approximately one-third of patients fail to improve after CRT based on current guideline recommendations and electrocardiographic criteria. Two-dimensional echocardiography and tissue Doppler-based techniques have shown variable results in assessment of left ventricular (LV) dyssynchrony and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Recently, two‐dimensional (2D) speckle‐tracking echocardiographic (STE) imaging is being performed frequently for assessment of cardiovascular diseases . Global longitudinal strain (GLS) and strain rate analyses using 2D STE are superior to conventional echocardiographic imaging for left ventricular function assessment .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two‐dimensional (2D) speckle‐tracking echocardiographic (STE) imaging is being performed frequently for assessment of cardiovascular diseases . Global longitudinal strain (GLS) and strain rate analyses using 2D STE are superior to conventional echocardiographic imaging for left ventricular function assessment .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that LV contraction occurs in a highly coordinated manner. Left ventricular systolic performance is affected not only by the contractile status of the myocardium, but also by the synchronicity of the myocardial segments . In fact, myocardial systolic dyssynchrony includes both differences in myocardial segment systolic amplitude and systolic peak time.…”
Section: Discussionmentioning
confidence: 99%
“…The 3DQ software displays the time‐volume tracings for each LV segment (pyramidal subvolume), and the time to minimum systolic volume is automatically identified for LV segments 16, 12, and 6. The 16R‐SDI, 12R‐SDI, 6R‐SDI parameters were calculated from the SD of LV segment (16, 12, 6) timings and are expressed as the percentage of the cardiac cycle as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional STE imaging has emerged as a useful modality when compared to either 2-D-STE or TDI for the ongoing evaluation of LV dyssynchrony [43]; however, prediction of both responses to CRT and LV reverse remodeling requires more studies with prospective data [44, 45]. …”
Section: Clinical Applicationsmentioning
confidence: 99%